2017
DOI: 10.1016/j.msea.2017.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Creep behavior of dissimilar metal weld joints between P91 and AISI 304

Abstract: Dissimilar welds between ferritic creep-resistant steels and austenitic stainless steels in power plant service are known to fail prematurely due to a large difference in their thermal coefficient of expansion. To address this problem, in the current work, modified 9Cr-1Mo steel (P91) and austenitic stainless steel (AISI 304) transition joints were produced using friction welding employing three interlayers: Inconel 625, Inconel 600, and Inconel 800H. These interlayers were friction welded one over another on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(17 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Several studies focusing on welding P91 steel with other materials, i.e., dissimilar joint, including P92 steel [29], PM2000 steel [30], AISI 304 stainless steel [31], and IASI 316L stainless steel [32], have also been carried out. The results are promising and some of the problems reported above when using P91/P91 joints seem to tend to be softened, depending on the welding process and conditions used.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies focusing on welding P91 steel with other materials, i.e., dissimilar joint, including P92 steel [29], PM2000 steel [30], AISI 304 stainless steel [31], and IASI 316L stainless steel [32], have also been carried out. The results are promising and some of the problems reported above when using P91/P91 joints seem to tend to be softened, depending on the welding process and conditions used.…”
Section: Introductionmentioning
confidence: 99%
“…Various works have been reported related to the dissimilar welded joint of P91 with austenitic alloys, such SS 304 [ 25 ], SS 316LN [ 26 ], SS 304L [ 27 , 28 ], and with nickel alloy interlayers of Incoloy 800H [ 11 , 29 ]. In these studies, the selection of nickel-based alloys is found to be beneficial, as they may provide a transition in terms of the coefficient of thermal expansion and have reportedly controlled carbon migration into the austenitic side.…”
Section: Introductionmentioning
confidence: 99%
“…Akram et al [12] welded dissimilar metals P21 and AISI304 through continuous drive friction welding and analysed the creep behaviour of the joints. Their work implied that a transgranular fracture mode was observed, and the damage was mainly due to the cavity growth.…”
Section: Introductionmentioning
confidence: 99%
“…Faying surface means the area where the physical contact takes place on the two parts during friction welding. However, the works related to faying surface modifications were not found in literature, many works for dissimilar joining on the combinations of different alloys like pure aluminium and AISI304L [8], AA6082 and Ti-6Al-4V [10], AISI304L and alloy steel [12], AISI1018 steel and AA6061-T6 aluminium [17], AA6061-T6 and AISI4340 [18], AA6061-T6 aluminium matrix composite and AISI304 [19], and titanium and AISI304 [20], To the best of knowledge, no such solid-state welding method was tried before joining steel AISI304L and aluminium AA6063-T6 rods with 100 mm length and 12 mm diameter with the welding parameters chosen in this paper. The selection of the materials was based on their different properties, such as melting point and their usage in various sectors.…”
Section: Introductionmentioning
confidence: 99%